2014
DOI: 10.1371/journal.pone.0111083
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Induces Apoptosis through a Ca2+-Mediated Mitochondrial Apoptotic Pathway in Human Umbilical Vein Endothelial Cells

Abstract: BackgroundHeat stress can be acutely cytotoxic, and heat stress-induced apoptosis is a prominent pathological feature of heat-related illnesses, although the precise mechanisms by which heat stress triggers apoptosis are poorly defined.MethodsThe percentages of viability and cell death were assessed by WST-1 and LDH release assays. Apoptosis was assayed by DNA fragmentation and caspase activity. Expression of cleaved PARP, Apaf-1, phospho-PERK, Phospho-eIF2a, ATF4, XBP-1s, ATF6, GRP78, phospho-IP3R, RYR and SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 52 publications
(66 reference statements)
3
64
0
Order By: Relevance
“…It has been reported that with the decline of SERCA2a level, myocardial cells lose their ability to transport calcium from the cytosol into the SR. The abnormal high cytoplasmic calcium level could result in mitochondrial permeability transition pore opening, ΔΨm decrease, and finally cause apoptosis of cardiomyocytes [32]. In addition, Lut can regulate cell apoptosis by enhancing autophagy [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that with the decline of SERCA2a level, myocardial cells lose their ability to transport calcium from the cytosol into the SR. The abnormal high cytoplasmic calcium level could result in mitochondrial permeability transition pore opening, ΔΨm decrease, and finally cause apoptosis of cardiomyocytes [32]. In addition, Lut can regulate cell apoptosis by enhancing autophagy [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mouse aortic endothelial cells from AMPK2 knockout mice showed higher expression of ERS markers such as XBP1, ATF6, GRP78, p-eIF2α, p-PERK, p-JNK and an increased level of intracellular Ca 2+ . Li et al [92] reported that heat stress activated UPR signaling through the PERK-eIF2α-ATF4, IRE1-XBP1s and ATF6 pathways in human umbilical vein endothelial cells. ERS also mediated aldosterone (Aldo)-induced apoptosis in vascular endothelial cells, as evidenced by increasing expression of GRP78 and CHOP.…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%
“…In the early phase of apoptosis, mitochondrial Ca 2+ release leads to an increase in intracellular Ca 2+ levels (Akopova et al, 2013). Sustained high levels of ROS likely promote destruction of organelle and cell membranes, as well as redistribution and continuous intracellular accumulation of Ca 2+ (Li et al, 2014). Thus, the generation of ROS and the increase in intracellular Ca 2+ concentration are interconnected during the progression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%